New Sensorless Sliding Mode Control of a Five-phase Permanent Magnet Synchronous Motor Drive Based on Sliding Mode Observer - Anissa Hosseyni; Ramzi Trabelsi; Sanjeeve Kumar; Med Faouzi Mimouni; Atif Iqbal (Institute of Advanced Engineering and Science, 2017)
This paper proposes a sensorless sliding mode control (SMC) for a five phase permanent magnet synchronous motor (PMSM) based on a sliding mode observer (SMO). The stability of the proposed strategy is proved in the sense of the Lyapunov theory. The sliding mode controller is designed with an integral switching surface and the sliding mode observer is developed for the estimation of rotor position and rotor speed. The proposed sensorless control strategy exhibits good dynamic response to disturbances. Simulation results are provided to prove the effectiveness of the proposed strategy.